Dendroarchaeology in Europe - Tegel, Willy; Muigg, Bernhard; Skiadaresis, Georgios; Vanmoerkerke, Jan; Seim, Andrea (Frontiers in Ecology and Evolution, 2022)
Abstract Human evolution was strongly related to environmental factors. Woodlands and their products played a key role in the production of tools and weapons, provided unique resources for constructions and fuel. Therefore wooden finds are essential in gaining insights into climatic and land use changes but also societal development during the Holocene. Dendroarchaeological investigations, based on tree rings, wood anatomy and techno-morphological characteristics are of great importance for a better understanding of past chronological processes as well as human-environment-interactions. Here we present an overview of the sources, methods and concepts of this interdisciplinary field of dendroarchaeology focusing on Europe, where several tree-ring chronologies span most of the Holocene. We describe research examples from different periods of human history and discuss the current state of field. The long settlement history in Europe provides a myriad of wooden archaeological samples not only for dating but also offer exciting new findings at the interface of natural and social sciences and the humanities.